The Impact of Teachers' Professional Development on The Internet Self-Efficacy and ICT Competencies - Murwaningsih, Tri (Data and Metadata, 2025)
Introduction: In the dynamic realm of education, the incorporation of Information and Communication Technology (ICT) has ushered in transformative shifts in the methods of teaching and learning. This study explores the impact of teacher professional development on the interconnected dimensions of internet self-efficacy and ICT competencies within the context of vocational high schools.Methods: The research employs a carefully designed survey instrument featuring 56 items, adapted from previous studies. Targeting vocational high school teachers across six Regencies in Central Java Province, Indonesia, the study utilized a clustered random sampling technique to select a sample size of 150 teachers in vocational high schools. The study employed Partial Least Square Structural Equation Modelling (PLS-SEM) to analyze the relationships among teacher professional development, internet self-efficacy, and ICT competencies.Results: This study yields four notable results. First, teachers' professional development positively impacts their internet self-efficacy. Second, teachers' professional development positively impacts their ICT competencies. Third, Teachers' internet self-efficacy influences their ICT competencies. Fourth, there is a mediated link between teacher professional development and ICT competencies through internet self-efficacy.Conclusions: This study underscores the importance of teacher personal professional development for improving internet self-efficacy and ICT competencies in vocational high schools. Policymakers should consider tailored training programs to enhance teacher skills, promoting better technology integration for improved vocational education.